The back pains of pet grooming - Gosiaco, Katherine Grace T. (Animo Repository, 2016)
Pet grooming is a task that involves the risk of developing musculoskeletal disorders as it involves physical activities that expose pet groomers to several awkward postures, forceful exertions, and repetitive motions. An initial investigation through Nordic musculoskeletal questionnaire (NMQ) suggests that majority of those engaged in this job experience musculoskeletal discomfort (MSDC) in the lower back. The study aims to develop a model of causation of MSDC taking into consideration tasks, tools and workplace factors and determine the significance of each through logistic regression (LR). Causes of MSDC were identified through review of related literature, personal interview and observation. Cause analysis was conducted to investigate the relationship of causes of lower back MSDC. A model that explains causes of MSDC was proposed in order to determine factors that will be included in the predictive mode of MSDC occurrence. Based on the causation model: (1) number of dogs groomed, (2) percentage of ill-tempered dogs, (3) percentage of long hair dogs groomed, (4, 5) back twisted during blow drying and cutting, as well as (6) deviation from sink to bottom reach significantly contribute to MSDC in the lower back. The model was assessed for goodness-of-fit tests and was found to be adequate.